2017
DOI: 10.1186/s12903-017-0384-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported negative experiences related to caries and its treatment among Swedish adult patients

Abstract: BackgroundIt has been suggested that dental caries should be regarded as a chronic disease as many individuals repeatedly develop new caries lesions. How this is perceived by caries active patients is unclear. The aim of this study was to measure patient-reported attitudes and negative experiences related to caries and dental treatment.MethodsA questionnaire was mailed to 134 caries active (CA) and 40 caries inactive (CI) adult patients treated at a Swedish public dental service clinic. The questionnaire inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
2
16
0
1
Order By: Relevance
“…Repeated cavities, root canal fillings, tooth extractions, and economic costs contributed to insight into the fact that dentists can restore teeth but that there will be no 'quick fix' for caries disease, an insight that adolescents had not formed [12]. Other studies found that adult patients with active caries who are aware of their caries situation [6,13] try to change their eating habits, use more fluoride, and receive more information about the caries disease and instruction on oral hygiene from the dental professionals compared to patients with inactive caries [5]. These findings are in line with the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated cavities, root canal fillings, tooth extractions, and economic costs contributed to insight into the fact that dentists can restore teeth but that there will be no 'quick fix' for caries disease, an insight that adolescents had not formed [12]. Other studies found that adult patients with active caries who are aware of their caries situation [6,13] try to change their eating habits, use more fluoride, and receive more information about the caries disease and instruction on oral hygiene from the dental professionals compared to patients with inactive caries [5]. These findings are in line with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This same study showed that preventive measures and non-operative treatment were associated with improvements in caries risk assessment and maintenance measures, but the extent of delivered treatment to high caries risk individuals was unacceptably low [5]. Another recent study investigating information and experiences related to caries and its treatment found that many caries active patients reported negative experiences [6]. Preventing caries disease in individuals who develop cavities under circumstances where most people can preserve health has obviously become a challenge for patients as well as dental health care professionals.…”
Section: Introductionmentioning
confidence: 93%
“…Participants talked about the value of TMP being prescribed by a dentist and at the same time being educated by dentists and members of a dental team on how to apply the product. It is well established in the literature that dentists' and dental team members' attitude towards patients can impact on treatment acceptance and home care compliance (9,(31)(32)(33)(34). In this study, nding a "different kind of dentist" who would not only " x teeth" meant that participants found someone who was dedicated to help them reach a status of having a "comfortable mouth with strong teeth".…”
Section: Transferability Of Ndings and Limitations Of The Studymentioning
confidence: 86%
“…Moreover, it is not clear to what extent data generated in such young subsets may be relevant for the use of those herbal products in the adult and geriatric population. This brings us back to the fact that the greater need is in the latter subpopulation: "there is a lack of evidence for caries preventive methods in adults with increased caries risk" [21,24]. It is also regrettable that in a number of trials the age of the participants was not reported, or reported only in general terms, such as "adult volunteers" or "different ages".…”
Section: Patient Demographicsmentioning
confidence: 99%
“…A slow shift is currently taking place in the dental profession, from a cyclic and repeated restorative approach based on filings to a population and individual prevention approach, restoration being seen rather as a last resort [23]. Nevertheless, it has been acknowledged that the interventions currently in use for the prevention of dental caries are not robustly rooted in scientific evidence, the majority of studies being derived from children and young patients, conducted without considering the caries risk of the subjects, and "there is a lack of evidence for caries preventive methods in adults with increased caries risk" [21,24]. Under the heading "Caries prophylactic agents", the ATC code (A01AA) developed by the World Health Organization recognizes only a number of four fluoride derivatives: sodium fluoride, sodium monofluorophosphate, olaflur, and stannous fluoride, as well as a number of fluoride combinations.…”
Section: Introductionmentioning
confidence: 99%